NON-PROMULGATION OF COVID-19 VACINATION AS MANDATORY IN THE REPUBLIC OF SERBIA - Srdjan, (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The first case of Covid-19 was registered in the Republic of Serbia on sixth of March 2020. Since the World Health Organization declared Covid-19 pandemic just five days later, especially because pandemic is still ongoing, it is apparent that the Republic of Serbia faced and is still facing a severe challenge.Once the infection began spreading, state introduced various economic, legal, and medical measures to lessen the negative effects of the pandemic, constantly modifying them to adjust rigidity of state response to the intensity of different waves of infection. Both singular and overall effects that adopted measures produced are interesting to study. Yet, it seems to us that the measures which were available, but not introduced, are at least as interesting to research. This refers specifically to mandatory vaccination.Two questions arise – what the reasons are why the measure was not introduced and what that actually means from legal perspective. In this paper focus is on later question. Specifically, we intend to offer possible interpretation of recommended but not mandatory vaccination, roles of participants, potential legal liability, all with reliance on normative method and different analytical techniques, with respect to theoretical achievements in medical law.
Keywords: mandatory vaccination; recommended vaccination; informed consent; civil liability; medical experiment; Covid-19; SARS-CoV-2